Exploration of space to achieve scientific breakthroughs - Prasad, Binod; Richter, Peter; Vadakedath, Nithya; Mancinelli, Rocco; Krüger, Marcus; Strauch, Sebastian M.; Grimm, Daniela; Darriet, Philippe; Chapel, Jean Paul; Cohen, Jacob; Lebert, Michael (Biotechnology Advances, 2020)
Living organisms adapt to changing environments using their amazing flexibility to remodel themselves by a process called evolution. Environmental stress causes selective pressure and is associated with genetic and phenotypic shifts for better modifications, maintenance, and functioning of organismal systems. The natural evolution process can be used in complement to rational strain engineering for the development of desired traits or phenotypes as well as for the production of novel biomaterials through the imposition of one or more selective pressures. Space provides a unique environment of stressors (e.g., weightlessness and high radiation) that organisms have never experienced on Earth. Cells in the outer space reorganize and develop or activate a range of molecular responses that lead to changes in cellular properties. Exposure of cells to the outer space will lead to the development of novel variants more efficiently than on Earth. For instance, natural crop varieties can be generated with higher nutrition value, yield, and improved features, such as resistance against high and low temperatures, salt stress, and microbial and pest attacks. The review summarizes the literature on the parameters of outer space that affect the growth and behavior of cells and organisms as well as complex colloidal systems. We illustrate an understanding of gravity-related basic biological mechanisms and enlighten the possibility to explore the outer space environment for application-oriented aspects. This will stimulate biological research in the pursuit of innovative approaches for the future of agriculture and health on Earth.
CRIS-Team Scopus Importer:2020-06-26
Keywords: Cancer research; Colloids; Epigenetics; Evolution; Horizontal gene transfer; Microgravity; Mutation; Space; Stress response; Tissue engineering